Role stressor as an antecedent of employees' family conflict: empirical evidence - Ismail, Azman; Wan Mahmood, Wan Hafizainee; Suhaimi, Fara Farihana; Abu Bakar, Rizal; Ismail, Yusof; Ahmad, Maisarah; Mohamad, Mohd Hamran; Ab Ghani, Asmuni (Alexandru Ioan Cuza University, Romania, 2014)
The role of stressors is recognized as a crucial human resource development and management issue where it can have an overpowering consequence on organizational and employee performance. This study was conducted to discover the relationship between role stressor and family conflict using self-report questionnaires gathered from academic staff of a public comprehensive university in Sarawak, Malaysia. The outcomes of SmartPLS path model revealed three findings: first, role ambiguity significantly correlated with family conflict. Second, role conflict significantly correlated with family conflict. Third, role overload significantly correlated with family conflict. This finding demonstrates that role stressor is recognized in employees’ family conflict. The paper provides discussions, implications and conclusion.